2007
DOI: 10.1017/s0959269506002638
|View full text |Cite
|
Sign up to set email alerts
|

Quelques éléments modaux dissociés dans le paragraphe oral dans des interviews en français L2 et L1

Abstract: Le propos de l'étude descriptive présentée dans cet article est de trouver des caractéristiques du discours de l'apprenant avancé en français L2. À cette fin, nous comparerons la production orale des apprenants avec celle des locuteurs natifs de français. Un trait du français parlé “spontané” (L1) est la dissociation d'un certain nombre de constituants discursifs du rhème, parmi ceux-ci des marqueurs du point de vue et des adverbes modalisateurs. Ces éléments devraient aussi être présents dans le discours d'un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 3 publications
0
13
0
2
Order By: Relevance
“…In order to contribute to the debate concerning the issue of whether it is possible for L2 learners to reach native-like levels in L2, we propose a combined analysis of three different linguistic levels, namely formulaic language (Forsberg 2006(Forsberg , 2008, information structure (Hancock 2007), and morpho-syntactic analysis (Bartning, to appear). Concerning information structure, earlier work has shown that it is fruitful to study the typical thematic parts of spoken French utterances, the so-called preambles and their various constituents (number, nature, functions, etc., Conway 2005;Hancock 2007).…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to contribute to the debate concerning the issue of whether it is possible for L2 learners to reach native-like levels in L2, we propose a combined analysis of three different linguistic levels, namely formulaic language (Forsberg 2006(Forsberg , 2008, information structure (Hancock 2007), and morpho-syntactic analysis (Bartning, to appear). Concerning information structure, earlier work has shown that it is fruitful to study the typical thematic parts of spoken French utterances, the so-called preambles and their various constituents (number, nature, functions, etc., Conway 2005;Hancock 2007).…”
Section: Preliminariesmentioning
confidence: 99%
“…Concerning information structure, earlier work has shown that it is fruitful to study the typical thematic parts of spoken French utterances, the so-called preambles and their various constituents (number, nature, functions, etc., Conway 2005;Hancock 2007). We look at these features as a measure of discursive and syntactic complexity for L2 French.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, they seem to correspond to the central communicative needs as enhancement/addition and moderation/restriction; vraiment and aussi function as intensifiers, peut-être and seulement as mitigators of linguistic constituents. With the exception of seulement they are also frequent adverbs in native speech production (Bilger, 2004;Chanet, 2004;Hancock, 2007;Sanell, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular we aim to describe late L2 discourse use of these adverbs. Syntactically, they differ with respect to their placement during the course of acquisition: while aussi and seulement move into the utterance from peripheral positions, left dissociation seem to be a late feature of vraiment and peut-être (Benazzo, 2000(Benazzo, , 2005Sanell, 2007;Hancock, 2007). Given the hypothesis that the use of these adverbs develops throughout acquisitional stages, we expect to find an increasing number of functions as learners progress through the stages.…”
mentioning
confidence: 97%